TO EVALUATION TEST OF QUALITY OF MAGNETIC FLUIDS FOR MAGNETOFLUID DEVICES - V. G. Bashtovoi; A. G. Reks; S. V. Klimovich; O. Yu. Volkova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Magnetic fluid is a colloid of magnetic nanoparticles. Using of magnetic fluids in technical devices demands applying of strong non-uniform magnetic fields for a long time. One of the most widespread magnetic fluid devices are magnetic fluid seals of mobile shafts, magnetic fluid supports, bearings, acceleration and angle of inclination gauges, devices for information input in the computer and etc. These devices demand high quality of used fluids. Processes of magnetophoresis and Brownian diffusion in magnetic fluid lead to concentration of magnetic particles in the areas with higher intensity of magnetic field and increase of fluid magnetization in these areas. A local change of particles concentration in the fluid leads to variation of its physical properties. Formation of aggregates from the particles and the further stratification of magnetic fluid, up to its destruction, may be the most serious consequence of redistribution of concentration of magnetic particles. These factors lead to variation of parameters of magnetic fluid devices; cause disturbance of their normal operation and even failure. Therefore, the consistent, high quality magnetic fluids which are not subject to fast stratification in a non-uniform magnetic field are necessary for effective work of the devices. The procedure of evaluation test of quality of magnetic fluids is proposed in this paper. The test is based on studying of influence of processes of magnetophoresis and Brownian diffusion of magnetic particles in magnetic fluid on the forces acting on the volume of fluid in an external non-uniform magnetic field. The procedure is developed on the basis of analysis of magnetic force variation in time under the action of non-uniform field of permanent magnets. Methods of determination of stability of magnetic fluid, known at present, demand rather complicated equipment and laborious and complex investigations. Proposed procedure can be used as an express method for evaluation of magnetic fluid quality for usage in technical devices, and it does not need complicated equipment.